STUDY OF ALPHA-FETOPROTEIN LEVELS IN CIRRHOTIC PATIENTS WITH HEPATOCELLULAR CARCINOMA - Tran Ha , Hieu; Nguyen Hoang , Khai; Pham Thanh , Binh; Đoan Vu , Nam; Le Nguyen Đinh , Hai; Đo Thanh , Tung; Nguyen Ngoc , Cuong (Tạp chí Y Dược Thực hành 175, 2024)
Objective: To investigate the serum alpha-fetoprotein (AFP) levels in cirrhotic patients with and without hepatocellular carcinoma (HCC). Subjects and methods: A cross-sectional descriptive study was conducted on 53 cases of cirrhosis at Military Hospital 175. We recorded 32 cases with HCC and 21 cases without HCC from January 2022 to January 2024. Results: AFP levels in the group of cirrhotic patients with HCC were significantly higher compared to those without HCC (p < 0.01). The AUROC of AFP levels for diagnosis of HCC in cirrhotic patients was good with an AUC of 0.841, p < 0.001. The AFP cut-off threshold ≥ 25.88 ng/ml had the highest value for diagnosing HCC in cirrhotic patients, with a sensitivity of 68.75% and a specificity of 95.24%. Conclusion: Serum AFP level was a commonly used test, and with a cut-off threshold ≥ 25.88 ng/ml, AFP had a sensitivity of 68.75% and a specificity of 95.24% in diagnosing HCC in cirrhotic patients.